2020
DOI: 10.1002/ijgo.13117
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pregnant Turkish women and Syrian refugees: Does living as a refugee have an unfavorable effect on pregnancy outcomes?

Abstract: Objective:To compare pregnant Turkish women and Syrian refugee women in terms of demographic data and obstetric and neonatal outcomes. Methods:In a retrospective study, the records of Turkish women and Syrian refugee women who gave birth at the Health Sciences examined. Maternal characteristics and obstetric and neonatal outcomes were compared between the two groups. Results:The study, which included 7950 Turkish women and 620 Syrian refugee women, found significant differences in maternal age according to nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 16 publications
3
25
2
Order By: Relevance
“…On the other hand, the rate of delivery by cesarean section and primary cesarean section were significantly higher in Turkish citizens in our study. In many studies in our country, it has been reported that cesarean section rates and primary cesarean rates are lower in Syrian refugees than Turkısh pregnant women 4,21,35 . This may be due to the referral of high‐risk patients to our tertiary hospital, as well as common medico‐legal problems related to Turkish pregnant women.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…On the other hand, the rate of delivery by cesarean section and primary cesarean section were significantly higher in Turkish citizens in our study. In many studies in our country, it has been reported that cesarean section rates and primary cesarean rates are lower in Syrian refugees than Turkısh pregnant women 4,21,35 . This may be due to the referral of high‐risk patients to our tertiary hospital, as well as common medico‐legal problems related to Turkish pregnant women.…”
Section: Discussionmentioning
confidence: 91%
“…This is called “healthy migrant effect” 41 . In the literature, better perinatal outcomes have been reported among Vietnamese refugees in Norway and Australia 32–45 . In addition, the rate of LBW in Mexican immigrants is reported to be better in the United States than in the native population (Latino health paradox) 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, while 3.1% of the babies of Syrian refugees had low birth weights, this rate was 7.7% among Turkish citizens; these rates were not significantly different. Although some Turkish studies in the literature support these findings [ 11 , 17 ], the available scientific evidence shows that being a refugee constitutes a disadvantage for neonatal weight [ 8 , 9 , 15 , 18 ]. The Republic of Turkey provides free health services to Syrian refugees and makes it easier for them to reach health resources.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was determined for key study objectives based on birth weight using OpenEpi with the following parameters: confidence interval (95% CI) 95%, power: 80%, ratio of Syrian/Turkish women: 1/3, mean birthweight TR : 3100 g, mean birthweight SY : 2900 g, and standard deviation: 500 based on research in the literature [ 9 , 14 , 15 ]. The sample size was a total of 277 high-risk pregnant women, with 213 Turkish citizens and 64 Syrian refugees.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation